ANALISIS EFEKTIVITAS PENGOLAHAN LIMBAH CAIR PADA PT PERTAMINA REFINERY UNIT V BALIKPAPAN - Mustakim (Jurnal Ilmiah Teknik Sipil TRANSUKMA, 2015)
The aim of research are to (1) to know waste water processing at Effluent Water Treatment Plant Refinery Unit V Balikpapan, (2) to know the waste water quality each of unit process of EWTP RU V Balikpapan, and (3) to know process cost effectiveness comparing with normal condition and value balance of EWTP RU V Balikpapan. The research has condcuted at June 2014 – July 2014 at Effluent Water Treatment Plant (EWTP) of PT. Pertamina Refinery Unit V Balikpapan. To know the process of waste water treatment at EWTP RU V Balikpapan is conducted by observing the 11 (eleven) units process such as (1) Refinery Waste Stilling Zone (RWSZ), (2) Gravity Separator, (3) Equalization Basin, (4) Coagulation Tank,(5) Dissolved Air Flotator, (6) Bio Aeration Basin, (7) Clarifier, (8) Gravity Head Discharge Chamber, (9) Storm Water Stilling Zone, (10) Storm Water Basin, dan (11) TPI Separator. There are 7(seven) of sample units and some parameters such as BOD (Biochemical Oxygen Demand ), COD (Chemical Oxygen Demand), oli and grease, dissolved sulfide (H2S), Amoniak (NH3), Phenol Total, temperature, pH dan debit of maximum waste water. The final result of research are BOD=13,7137,COD = 37,7067, oil and grease = 1,6, H2S = unidentified, phenol total = unidentified, Temperature = 29,10c, TDS = 136 mg/l, Debit Max = 500 m3/Hr, Design RainWaste Water = 2400 m3 /Hr).